2020
DOI: 10.1108/jeim-06-2019-0148
|View full text |Cite
|
Sign up to set email alerts
|

What drives organizations to switch to cloud ERP systems? The impacts of enablers and inhibitors

Abstract: PurposeSwitching to public cloud enterprise resource planning (ERP) systems not only provides financial and functional benefits to organizations, but also results in sunk costs of incumbent systems and uncertainty costs of cloud systems. The purpose of this study is to investigate the enablers and inhibitors concerning switching to cloud ERP systems at the organizational level.Design/methodology/approachData were collected from 212 top managers and owners of the enterprises in Taiwan, and 10 hypotheses were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…There have been studies conducted in Europe, South Africa, Egypt, and Taiwan. Yu-Wei Chang [35] explored the enablers and inhibitors that drive organizations to switch to cloud-based ERP systems. EPR packages are mainly used in Korea and Japan in Asia, while few studies have been conducted in Korea or Japan.…”
Section: Cloud-based Erp Adoptionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been studies conducted in Europe, South Africa, Egypt, and Taiwan. Yu-Wei Chang [35] explored the enablers and inhibitors that drive organizations to switch to cloud-based ERP systems. EPR packages are mainly used in Korea and Japan in Asia, while few studies have been conducted in Korea or Japan.…”
Section: Cloud-based Erp Adoptionmentioning
confidence: 99%
“…AlBar and Hoque [6] also investigated cloud-based ERP adoption intention based on the TOE framework, and found that ICT skill, ICT infrastructure, top management support, regulatory environment, and competitive environment were significantly related to cloud-based ERP adoption, while organizational culture was not significantly related. Yu-Wei Chang [35] studied cloud-based ERP switching intention using the TOE framework, and discovered that financial advantage, system quality, and industry pressure were significantly related to cloud-based ERP switching intention, while information quality and government support were not significantly related.…”
Section: Technology-organization-environment (Toe) Frameworkmentioning
confidence: 99%
See 3 more Smart Citations